Sports Biomechanics Research on the Hammer Throw: Systematic Review - Muchamad Arif Al Ardha; Nurhasan Nurhasan; Catur Supriyanto; Fifit Yeti Wulandari; Chung Bing Yang; Ju Han Lin; Novadri AYUBI; Awang Firmansyah; Sauqi Sawa Bikalawan; Ainun Zulfikar Rizki; Rizki Satrio Utomo; Kukuh Pambuka Putra; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to evaluate the critical role of sports biomechanics in enhancing the performance and technique of athletes participating in the challenging discipline of Hammer Throw. This research uses a systematic review method by searching various jour-nal databases such as Scopus, Web of Science, PubMed, and Embase. The keywords used are sports biomechanics, kinetic analysis, kinematic analysis, and gait analysis in hammer throwing. The inclusion criteria in this research are articles published in the last 5 years starting from 2023. Furthermore, the exclusion criteria in this research are articles published in disreputable journals. A total of 1,147 articles from journal databases were identified. There were 8 articles that met the requirements and were selected for this systematic review. The review identified specific improvements in athletes' technique precision and performance consistency attributed to biome-chanical interventions. Moreover, it underscored the efficacy of biomechanical analysis in developing targeted coaching strategies. The synthesis of these articles reveals that sports biomechanics substantially contributes to advancing hammer throwing by enabling detailed analysis and feedback, enhancing athlete development, and refining coaching methods. Conclusively, the integration of biomechanical data and technology is proving indispensable for pushing performance boundaries in hammer throw. Future research should close exist-ing knowledge gaps and further investigate the impact of digital and biofeedback methods on athlete performance, offering a roadmap for scientific progress in the sport. These studies hold the potential to enhance athletes' performance and contribute to the scientific advancement of hammer throwing as a sport.